Multidimensional Scaling Approach to Evaluate the Level of Community Forestry Sustainability in Babak Watershed, Lombok Island, West Nusa Tenggara - Nandini, Ryke; Kusumandari, Ambar; Gunawan, Totok; Sadono, Ronggo (Universitas Muhammadiyah Surakarta, 2017)
Community forestry in Babak watershed is one of the efforts to reduce critical land area. The aim of this research was to evaluate the level of community forestry sustainability in both of community forest (HKm) and private forest in Babak watershed. Multidimensional scaling (MDS) was used to analyse the level of community forest sustainability based on the five dimensions of ecology, economy, social, institutional, and technology as well as 29 attributes. Leverage analysis was used to know the sensitive attributes of sustainability, while Monte Carlo analysis and goodness of fit was used to find the accuracy of MDS analysis. The result shows that HKm was in moderate sustainability level (sustainability index 54.08%) and private forest was in less sustainability level (sustainability index 48.53%). Furthermore, the ecology and technology in HKm were classified as less sustainable, while the institution and technology in private forest were considered less sustainable. There were 11 sensitive attributes of HKm and 19 sensitive attributes of private forest. The priorities of attribute improvement in HKm include land recovering (the dimension of ecology) and cooperative development (the dimension of technology). In private forest, the priorities of attribute improvement include leadership capacity building (the institutional dimension) and also the use of silviculture intensive and soil conservation (the dimension of technology).